Contribution to Chaetosphaeriaceae—Kionochaeta setosimplicia sp. nov. from Thailand - Nuankaew, Salilaporn; Chuaseeharonnachai, Charuwan; Somrithipol, Sayanh; Kwantong, Papichaya; Srihom, Charisa; Ros, Chandapheakdey; Boonyuen, Nattawut (Phytotaxa, 2021)
Species of Kionochaeta are saprobes commonly associated with decaying plant materials. As a part of surveys on freshwater microfungi, Kionochaeta-like taxon was found on a submerged decaying twig at a rivulet in the protected forest area of Khao Kheow Open Zoo (KKOZ), eastern Thailand. This taxon is microscopically similar to Kionochaeta, but clearly differs by its accessory lateral setiform branches and sterile setae arising beside the conidiophores. Multi-locus phylogenies inferred from four combined loci (SSU, ITS, LSU and RPB2) demonstrated that this taxon clustered as a unique clade with Kionochaeta species (Chaetosphaeriaceae, Chaetosphaeriales). Therefore, we introduce this taxon as K. setosimplicia, and it is phylogenetically close to K. castaneae, K. ramifera and K. pughii. Kionochaeta setosimplicia is separated from K. microspora and K. spissa. In Kionochaeta clade 1, K. nanophora forms a basal taxon. Kionochaeta ivoriensis forms a distinct Kionochaeta clade 2 distant from other Kionochaeta.